The in vitro hepatic metabolism of 1-phenyl-2-(2-benzothiazolinone-3-yl)ethanone and their reduced derivatives - (:unkn) unknown (GUSTAV FISCHER VERLAG, 1999)
The in vitro hepatic microsomal metabolism of 1-phenyI-2- (2-benzothiazolinone-3 -yl)ethanone (I) and (9)-1-Phenyl-2-(2-benzothiazolinone-3-yl)ethanol (II)) was studied using both rat microsomal preparations and soluble fractions fortified with NADPH. These two substrates and their potential dealkylation metabolite 2-benzothiazoIinone were synthesized and their structures were elucidated by spectral methods. The results showed that (I) was metabolised to (LI), the corresponding alcohol by reduction. More alcohol metabolite was observed with microsomes than those obtained with the soluble fractions. No dealkylation of (I) was observed in the experiments using both microsomes and soluble fractions. (II) was metabolised to (I), the corresponding ketone by oxidation. However, compared to the metabolism of (I), more ketone metabolite was observed with soluble fractions than microsomes;(II) was also dealkylated to (III) with only soluble fractions but no dealkylated metabolites were found in the microsomes. In addition, a common unknown metabolite was observed with each substrates.
Keywords: hepatic metabolism; liver, metabolism; benzothiazolone; microsomal metabolism; alcohol; ketone